Будни: стихи / Николай Година - Година Николай Иванович (Современник, 1990)
Экземпляры: аб (ретроконверсия) / Инвентарный номер: 28594 / Цена: 0.20 / Сис.шифр: Р2 / Авт.знак: Г 59 / ГРНТИ: 17.82.10 / ББК: 84(2=411.2)6